PENDIDIKAN KESEHATAN MELALUI PENYULUHAN TENTANG MAKANAN SEHAT DAN DAMPAK KONSUMSI MIE INSTAN BAGI KESEHATAN DI DESA DRENGES KEC. SUGIH WARAS KAB. BOJONEGORO - Prasetyo Handrianto; Ratih Kusuma Wardani; Fitriana Ikhtiarinawati Fajrin (Journal of Science and Social Development, 2018)
Many community activities make people tend to look for something that is instant for consumption, one of which is consuming instant noodles. People assume that instant noodles have good nutrition for consumption, not even a few who classify as nutritious food. The low level of knowledge can be due to the fact that the advertising process circulating in the media, especially television, is not balanced with education about healthy food from related parties. Then knowledge is very important to provide understanding to the community by transferring knowledge through education. To overcome this, a health education for the community is needed in the form of counseling about healthy food and the impact of instant noodles on health. This research is descriptive quantitative with cross sectional data collection techniques namely questionnaire distribution and questionnaire collection which is carried out on one day. Counseling was carried out in Drenges village, Sugihwaras Bojonegoro Sub-district in 2018 with 82 respondents. The results showed that based on the level of knowledge, the community with a lack of knowledge was 58.5% and the level of knowledge was 41.5%. The average community consumes instant noodles once a week at 52.2%, the rest consumes more than 1 time per week. As many as 92% consume a total of 1 pack, the sisan consumes more than one pack per serving. The types of additives used by the public in consuming instant noodles are varied, ranging from eggs, sliced ​​meat, tofu, tempeh, mustard greens, cabbage, carrots, tomatoes, beans, crackers, rice, but there are some people who consume noodles without adding additional ingredients. Most additives or commonly used by the majority of the community are eggs that are 30%. The community consumes instant noodles almost every meal time, both breakfast lunch and dinner. Even some people consume noodles outside meals. The majority of the community or as much as 52% consume instant noodles at breakfast time or as breakfast. The presentation of the community consists of 2, namely with gravy and serving in a fried manner. But most or as much as 53.7% of the community presents with a dish of gravy and 28.3% presents in a fried way. The conclusion of this community service is health education with counseling methods about healthy food and the impact of instant noodle food on health is very effective in increasing the level of public knowledge about healthy food and the impact of instant noodle food on health. It is expected that by increasing the level of public knowledge can change people's behavior about the daily diet that is done by them.